The Pilgrims of Plimoth - Sewall, Marcia (New York : Atheneum, 1986)
Chronicles, in text and illustrations, the day-to-day life of the early Pilgrims in the Plimoth Colony.
Keywords: Massachusetts -- Social life and customs -- To 1775 -- Juvenile literature